Relation between Smartphone Addiction, Sleep Quality and Psychological Health among adolescents in Malaysia - Abdullah , Hilwa (International Journal of Psychosocial Rehabilitation, 2020)
Dependency on digital causes today’s generation to have inactive lifestyle that could instigate negative impact towards health, social interaction and individual intellectual skill. Besides affecting individual’s sleeping time, smartphone addiction can disturb a person psychological well-being. This research was carried out to identify the relationship of smartphone addictions with sleep quality with psychological health of Kolej PERMATA Insan’s (KPI), Universiti Sains Islam Malaysia (USIM) students. Research respondents were 158 KPI students comprise of 76 male students and 82 female students aged between 13 to 16. A set of questionnaires consisted of four parts have been distributed to all respondents in order to acquire their information. The questionnaire comprised of demographic section; the instruments Smartphone Addiction Scale (SAS), Pittsburgh Sleep Quality Index (PSQI) and General Health Question-12 (GHQ-12).Findings shown there were significant relationship between smartphone addiction and sleep quality with mental health (p<0.05).The level of smartphone addiction and sleep quality with respondents’ psychological health were correlated. Demographically, 51.9% respondents were addicted towards smartphone, 65.2% respondents have weak sleep quality and 64.6% respondents have a worrying state of psychological health. This research suggests that smartphone addiction level must be reduced, and sleep quality must be increased in order to ensure a good mental health level.